Mechanisms of implicit learning : connectionist models of sequence processing - Cleermans, Axel (Cambridge, Mass. ; London : MIT, 1993)
Implicit learning: Explorations in basic cognition
The SRN model: Computational aspects of sequence processing
Learning a finite-state grammar
Discovering and using path information
Encoding nonlocal context
Sequence learning as a paradigm for studying implicit learning
Learning the structure of event sequences
Sequence learning: Further explorations
Sequence learning and memory disorders
Attention and sequence structure
Elementary sequence learning and the effects of explicit knowledge
Encoding remote context
Long-distance contingencies and prediction-based learning
Comparison with other architectures for sequence processing
Explicit sequence learning
An explicit prediction task
Transfer to new material
General discussion
Prediction-relevance and context representation
Attention, awareness, and the role of explicit knowledge
Conscious and unconscious knowledge
Transfer and abstraction
Bibliografija iza svakog poglavlja
Kazalo
Keywords: implicitno učenje; neuralne mreže; konekcionističke teorije